Vegetative Propagation of Dendrocalamus strictus through Macro-proliferation-II - Kumar, Adarsh; Gupta, B. B.; Negi, D. S. (Indian Forester, 1991)
The earlier study of eight months i.e., August to March (Adarsh Kumar et al., 1988) on vegetative propagation of Dendrocalamus strictus through macro-proliferation was extended by another four months i.e., April to July in order to study the growth behaviour in full one year. It has been found that sufficient number of field plantable propagules can be developed through seedling multiplication. The propagules thus produced. Planted in the field established well and showed culm formation in six months.